2020
DOI: 10.3389/feart.2020.00333
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Discharge of Dissolved Methane in the Middle Okinawa Trough, East China Sea

Abstract: Widespread seepage of methane from seafloor sediments on continental margins are released into seawater, a portion of which may escape to the atmosphere. To assess the water column distribution characteristics of methane and its input to the atmosphere, we investigated methane emissions from the shelf and west slope of the back-arc Okinawa Trough (OT), East China Sea. Our results showed a heterogeneity distribution of methane within the water column. The highest value, which was more than 10 times of the backg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…Gas hydrates are mainly found in continental margins as well as in permafrost regions, which are formed in marine sediment under relatively low temperatures and high pressures. Having been viewed as a potential resource, the hydrates are not merely the targets of offshore drilling, infrastructure, and slope stability assessment, but also play a vital role in the study of global climate change and the carbon cycling (Kvenvolden, 2000;Zhang et al, 2020;Kars et al, 2021;Yao et al, 2021;Yu et al, 2022). Therefore, submarine hydrate identification has been of great interest to academic and related industries in recent years (Li et al, 2016;Becker et al, 2020;Merle et al, 2021;Wang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Gas hydrates are mainly found in continental margins as well as in permafrost regions, which are formed in marine sediment under relatively low temperatures and high pressures. Having been viewed as a potential resource, the hydrates are not merely the targets of offshore drilling, infrastructure, and slope stability assessment, but also play a vital role in the study of global climate change and the carbon cycling (Kvenvolden, 2000;Zhang et al, 2020;Kars et al, 2021;Yao et al, 2021;Yu et al, 2022). Therefore, submarine hydrate identification has been of great interest to academic and related industries in recent years (Li et al, 2016;Becker et al, 2020;Merle et al, 2021;Wang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…According to the study by Sun et al [18], the surface dissolved CH4 concentration in the East China Sea (ECS) was 4.9 ± 3.2 nM, the saturation was 203 ± 126%, and the sea-to-air flux was 9.77 ± 16.0 μmol/m 2 /d. While another study found that in the continental shelf of ECS, the surface dissolved CH4 concentration was 12.5 ± 3.79 nM, the saturation was 675.86 ± 204.37%, and the sea-to-air flux was 54.75 ± 19.38 μmol/m 2 /d [10]. In the South China Sea, the surface dissolved CH4 concentration was 4.5 ± 3.6 nM, the saturation was 230 ± 184%, and the sea-to-air flux was 8.6 ± 6.4 μmol/m 2 /d [19].…”
Section: The Surface Dissolved Ch4 Concentration and Sea-toair Flux I...mentioning
confidence: 93%
“…In recent years, due to the sharp increase of activities such as the input of terrestrial rivers, oil and gas field exploitation, land reclamation, and mariculture, the sources and sinks of dissolved CH4 in the marine are diversified, and its concentration and sea-air exchange flux show a new feature of more intense spatio-temporal evolution, and its contribution to atmospheric CH4 continue to increase [5,8]. Therefore, scholars have made a lot of observations on dissolved CH4 in estuaries, open seas, and continental shelves [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The most important contributors to the dissolved carbon in the seawater are hydrothermal vents and cold seeps, and the DIC through the latter ones constitutes up to 14.3% of the total amount in the seawater [49]. The enhanced concentration of the dissolved methane was detected in the western slope of the MOT, and the value of 24.7 nM is ten times higher than the background concentration [50]. The sea-to-air flux of methane can reach up to 116 μmol m -2 d -1 , and the average values higher than those in other known oceans indicate the MOT is rich in methane, which discharges into the seawater and even the atmosphere from the seabed at present [50].…”
Section: Water Columnmentioning
confidence: 95%
“…The studies of the seawater in the OT are aimed at pinpointing the sites of the enhanced concentration of dissolved methane, assessing the origin of the carbon, and figuring out the methane flux at the sedimentseafloor and the sea-air interfaces [42,49,50]. The most important contributors to the dissolved carbon in the seawater are hydrothermal vents and cold seeps, and the DIC through the latter ones constitutes up to 14.3% of the total amount in the seawater [49].…”
Section: Water Columnmentioning
confidence: 99%